Direct estimation of de novo mutation rates in a chimpanzee parent-offspring trio by ultra-deep whole genome sequencing. Issue 1 (December 2017) - Tatsumoto, Shoji; Go, Yasuhiro; Fukuta, Kentaro; Noguchi, Hideki; Hayakawa, Takashi; Tomonaga, Masaki; Hirai, Hirohisa; Matsuzawa, Tetsuro; Agata, Kiyokazu; Fujiyama, Asao
Abstract Mutations generate genetic variation and are a major driving force of evolution. Therefore, examining mutation rates and modes are essential for understanding the genetic basis of the physiology and evolution of organisms. Here, we aim to identify germlinede novo mutations through the whole-genome surveyance of Mendelian inheritance error sites (MIEs), those not inherited through the Mendelian inheritance manner from either of the parents, using ultra-deep whole genome sequences (>150-fold) from a chimpanzee parent-offspring trio. We identified such 889 MIEs and classified them into four categories based on the pattern of inheritance and the sequence read depth: [i]de novo single nucleotide variants (SNVs), [ii] copy number neutral inherited variants, [iii] hemizygous deletion inherited variants, and [iv]de novo copy number variants (CNVs). Fromde novo SNV candidates, we estimated a germlinede novo SNV mutation rate as 1.48 × 10−8 per site per generation or 0.62 × 10−9 per site per year. In summary, this study demonstrates the significance of ultra-deep whole genome sequencing not only for the direct estimation of mutation rates but also for discerning various mutation modes includingde novo allelic conversion andde novo CNVs by identifying MIEs through the transmission of genomes from parents to offspring.